The environment as a public issue: policies, actors and territories (Desarrollo, Estado y Espacio, 2024)
This Dossier seeks to contribute to the debates on development, state and space from approaches focused on the environmental issue. The choice of this thematic axis is based on the understanding that environmental processes and problems are a key mark of current geographies and that, therefore, they strain the possibilities and scope of development policies, as well as the spatial projects associated with them. The seven articles that make up the dossier address issues such as: agroecological transition trajectories, controversies over the contamination of bodies of water, environmental regulations and access to justice, nature conservation policies and policies for the (un)protection of native forests and wetlands, infrastructure for global connectivity and flood risk, links between mining extractivism and energy transition.
Keywords: environment; public policies; territory; development